Generation of transgenic‐cloned Huanjiang Xiang pigs systemically expressing enhanced green fluorescent protein. (5th September 2018) - Zhu, Xiang‐Xing; Zhong, Yi‐Zhi; Ge, Yao‐Wen; Lu, Ke‐Huan; Lu, Sheng‐Sheng
Contents: Huanjiang Xiang pig is a unique native minipig breed originating in Guangxi, China, and has great utility value in agriculture and biomedicine. Reproductive biotechnologies such as somatic cell nuclear transfer (SCNT) and SCNT‐mediated genetic modification show great potential value in genetic preservation and utilization of Huanjiang Xiang pigs. Our previous work has successfully produced cloned and transgenic‐cloned embryos using somatic cells from a Huanjiang Xiang pig. In this study, we firstly report the generation of transgenic‐cloned Huanjiang Xiang pigs carrying an enhanced green fluorescent protein (eGFP) gene. A total of 504 SCNT‐derived embryos were transferred to two surrogate recipients, one of which became pregnant and gave birth to three live piglets. Exogenous eGFP transgene had integrated in all of the three Huanjiang Xiang piglets identified by genotyping. Furthermore, expression of eGFP was also detected from in vitro cultured skin fibroblast cells and various organs or tissues from positive transgenic‐cloned Huanjiang Xiang pigs. The present work provides a practical method to preserve this unique genetic resource and also lays a foundation for genetic modification of Huanjiang Xiang pigs with improved values in agriculture and biomedicine.